Prosedur Hukum dalam Mendapatkan Hak Pemulihan bagi Korban - Shindu Prastu Qildi Wibowo Mukti; Abd. Wachid Habibullah (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
Restoration for victims of criminal acts is an essential aspect of the judicial system that is often overlooked. Law enforcement efforts tend to focus on perpetrators, while victims' rights, including physical, psychological, and financial recovery, remain neglected. The case of Een's murder and arson serves as an example where restitution and compensation rights were not clearly accommodated in legal proceedings. This article aims to examine the legal procedures available to victims or their families in obtaining restoration rights. The discussion includes criminal law aspects such as restitution and compensation based on Law No. 13 of 2006 jo. Law No. 31 of 2014 on Witness and Victim Protection, as well as the Criminal Procedure Code (KUHAP). Additionally, this article highlights the civil law route through lawsuits based on Article 1365 of the Civil Code regarding unlawful acts (KUHAPER). With a normative juridical approach and internship experience at the Legal Consultation and Assistance Clinic of Trunojoyo Madura University, this article is expected to contribute to strengthening victims' rights within the Indonesian legal system through the available legal avenues, both criminal and civil.